The Influence Of Task Complexity, Behavioral Accounting And Professionalism On Auditor Performance With Emotional Spiritual Quotient As An Intervening Variable - Didi Sujadi; Sugiyanto, Sugiyanto; Endang Ruhiyat (Jurnal Ekonomi, 2024)
This research aims to determine the influence of task complexity, behavioral accounting , and professionalism on auditor performance with emotional spiritual quent as an intervening variable. The population in this study was 105 Public Accounting Firms in the South Jakarta area registered with the Indonesian Institute of Public Accountants (IAPI) in 2023. Samples were drawn using a purposive sampling technique. The results of distributing the sample questionnaire were 77 respondents. This research method is quantitative and the type of data used is primary data. Data was obtained through questionnaires distributed to auditors working at Public Accounting Firms in South Jakarta who were registered with the Indonesian Institute of Public Accountants (IAP I ) in 2023. The data analysis test technique used was Path Analysis using SPSS 22. The results of this study show that partially the task complexity variable has no direct effect on auditor performance, while behavioral accounting and professionalism have a direct positive effect on auditor performance. Intervening results of task complexity and professionalism does not mediate the auditor's performance through the emotional spiritual quotient, while behavioral accounting mediates the relationship between the auditor's performance through the emotional spiritual quotient, and the emotional spiritual quotient has a positive effect on the auditor's performance.